Prevalence of antibiotic residues in milk samples of small-scale dairy households in Bengaluru, India - MURUGESAN, DEVI; SHOME, BIBEK RANJAN; VENUGOPAL, NIMITA; M, PRAVEEN KUMAR A; TEWARI, RITUPARNA; REVANAIAH, YOGISHARADHYA; KUMAR, NARESH; PAPANNA, MOHAN; SHOME, RAJESWARI (The Indian Journal of Animal Sciences, 2023)
This study aimed to estimate the burden of subclinical mastitis in community setting, animal handlers’ knowledge, attitude and practices on mastitis and antibiotic use, and to detect antibiotic residues in milk samples. A total of 211 households belonging to four clusters of Karnataka state in Southern province of India were selected through 30-cluster approach. A total of 380 milk samples were analyzed for Subclinical Mastitis (SCM) by California Mastitis Test (CMT) and antibiotic residues by spore-based and Charm Rosa tests. Animal handler’s basic knowledge, attitude and practices (KAP) on antibiotics use were recorded. SCM prevalence was found 42% in the study site; antibiotic residues were detected in 21% (79/380) of milk samples; 7.1% and 5.52% of samples had maximum residual limits (MRL) and Multi Drug Residues (MDR), respectively. Antibiotic residues were detected in 32.22% of the households. Majority of animal handlers heard about antibiotics (83.31%), 51% of handlers treated the animals on their own and 23% of them bought antibiotics without prescription. High prevalence of SCM in the study setting and antibiotic load in milk samples raise food safety concern. Regulatory measures for prudent antibiotic use and knowledge dissemination among animal handlers for clean milk production are the measures required to tackle the problem.